Annual Primary Care 2030 Convening: Creating an Enabling Ecosystem for Person-Centered Primary Healthcare Models to Achieve Universal Health Coverage in Low- and Middle-Income Countries - Jessica L. Alpert; Sofiat Akinola; Edward Booty; Dessislava Dimitrova; Thu T. Do; Audu Lucky Emmanuel; Pascal Fröhlicher; Caroline W. Gitonga; Phan Le Thu Hang; Lindsay Hunt; Salim Hussein; Helen Kiarie; et al. (Annals of Global Health, 2020)
Background: The 2019 United Nations General Assembly High-Level Meeting on Universal Health Coverage and the 2018 Declaration of Astana reaffirm the highest level of political commitment by United Nations Member States to achieve access to health services and primary healthcare for all. Both documents emphasize the importance of person-centered care in both healthcare services and systems design. However, there is limited consensus on how to build a strong primary healthcare system to achieve these goals. Methods: We convened a diverse group of global stakeholders for a high-level dialogue on how to create a person-centered primary healthcare system, using the country examples of the Republic of Kenya and the Socialist Republic of Vietnam. We focused our discussion on four themes to enable the creation of person-centered primary healthcare systems in Kenya and Vietnam: (1) strengthened community, person and patient engagement in subnational and national decision making; (2) improved service delivery; (3) impactful use of innovation and technology; and (4) meaningful and timely use of measurement and data. Findings: Here, we present a summary of our convening’s proceedings, with specific insights on how to enable a person-centered primary healthcare system within each of these four domains. Conclusions: Following the 2019 United Nations General Assembly High-Level Meeting on Universal Health Coverage and the 2018 Declaration of Astana, there is high-level commitment and global consensus that a person-centered approach is necessary to achieve high-quality primary healthcare and universal health coverage. We offer our recommendations to the global community to catalyze further discourse and inform policy-making and program development on the path to Universal Health Coverage by 2030.